Yıldız seyirci ilişkisi bağlamında Türkan Şoray'ın yıldız kimliği - Usta, Ebra (My University, 2021)
Yıldız kavramını anlamak, toplumu anlamak açısından önemlidir. Bir zamanlar dünyaya hakim olan yıldızlık sistemi, Yeşilçam döneminde Türkiye sinemasının da önemli bir ayağı olmuştur. Türkan Şoray ise Türkiye sinemasındaki en önemli, en çok baş rol oynayan yıldızlardan biridir. Bu tezde yıldızın üretimi, pazarlaması ve tüketimi, Yeşilçam döneminde yıldızlık, Türkan Şoray'ın kariyerini inşa etme süreci ve dönüşümü incelenmiş; Türkan Şoray'ın seyirciyle ilişkisi Foto Roman Dergisi’ndeki köşe yazılarıyla anlatılmıştır.

Understanding the concept of stardom is important in understanding society. Starsystem, which has once dominated the world, has been a major pillar of the cinema in Turkey during the Yeşilçam period. In this context, Turkan Soray is one of the most important actors to play in lead roles during this time in Turkey. In this thesis, stardom, production, marketing and consumption of the star, stardom in the Yeşilçam period, the process of building Türkan Şoray's career and its transformation were examined; and Türkan Şoray's relationship with the audience was explained through her column in Foto Roman Magazine.
Keywords: Actors and actresses; Aktörler ve aktrisler; Audience; Biography; Biyografi; Cinema; Criticism and interpretation; Dergi Türkan Şoray; Eleştiri ve yorum; Magazine; Motion pictures; Seyirci; Sinema; Stardom; Şoray, Türkan, 1945-; Turkey; Türkan Şoray; Türkiye; Yıldızlık